Wheelchair market trends for people with disabilities in Paraguay: year 2022. - Gustavo Ortiz; Eladio Quintana; Eduardo Ortigoza; Liz Cabañas (Población y Desarrollo, 2023)
This research gathers historical information about the supply and demand of wheelchairs in Paraguay and its projection. Indeed, the main objective of the work, is to determine the market trends of wheelchairs for people with disabilities in Paraguay, with data collected from 2018 to 2021. To reach the proposed objective, a literature review was conducted, consulting primary and secondary sources of information, then an in-depth quantitative and qualitative documentary research was conducted, based on information from public and private organizations related to the purchase, sale and use of wheelchairs in Paraguay. This research allows to have in a single document, the current status and future trends of the industry. The particular contribution of this study is to provide information from various sources on the commercialization and use of wheelchairs in Paraguay, in such a way that it serves as a source of consultation for different interest groups, such as companies, public institutions, non-governmental organizations that provide services and end users, who in many cases cannot access useful and detailed information.